Multidisciplinary approach to matricide and post-mortem cannibalism: Integrating medico-legal and psychiatric investigations - Matteo Antonio Sacco; Alessandro Santurro; Francesca Consalvo; Saverio Gualtieri; Luigi Mastrangelo; Pietrantonio Ricci; Isabella Aquila (Forensic Science International: Synergy, 2025)
Cannibalism is a practice documented since prehistoric times, with diversified motives. In the modern society, cannibalism is rare and often carried out in serious psychiatric contexts. Some authors have highlighted the association of these events with stories of family abuse and conflictual parental relationships. Forensic investigations can be complicated due to decomposition, dismemberment and the concealment or ingestion of entire parts of the corpse. We report a singular case of matricide. A woman was found brutally murdered in her home with anatomical parts of the body found scattered in the kitchen and in the freezer of the house. A scene analysis, an autopsy and criminological investigations using the psychological autopsy method were carried out. Forensic investigations proved that the cohabiting son had killed the woman using a blunt instrument causing her a head trauma and had subsequently dismembered the corpse by carrying out necrocannibalism. The psychological autopsy revealed that the man suffered from severe schizophrenia not treated with drugs and that he had previously attempted to attack his mother on other occasions. The study traces, through literature review, the medico-legal and psychiatric implications in cannibalism and emphasizes the need for prevention of these events through active psychiatric surveillance.